Communication, Pashtun Culture, and Decision-making about the Polio Vaccine - Khan, Mohammad Anwar; Jan, Faizullah (Journal of Peace, Development and Communication, 2024)
This research study focuses on the conceptualization and theorization of health communication within the culture centered approach, contributing towards an understanding of the cultural dynamics of public health emergencies like infections disease. The cultural centered approach, contesting against the western biomedical models of health communication, suggests alternative methodologies to co-construct meanings of health by engaging in direct dialogue with communities. In this project one such global challenge, Poliomyelitis (Polio), a highly contagious and incurable viral disease, mostly affecting children under five years of age, a well-established and accepted cause of irreversible paralysis and sometimes leading to death. The Global Polio Eradication Initiative (GPEI) was launched in 1988 globally and is facing serious challenges to eradicate poliovirus consistently lingering on in the last two endemic countries - Pakistan and Afghanistan. In this study, 27 semi-structured in-depth interviews with an ethnic Pashtun parent- polio vaccine refusal cases, from three high risk districts of Khyber-Pakhtunkhwa, Pakistan. These interviews were analyzed using constructivists grounded theory to explore how the life experiences of these cultural participants shape their understanding of health, consequently, make decisions regarding immunization of their children against poliovirus. Further, develop an understanding of the cultural constructions of health, emerged four concepts resultantly: honoring familial hierarchy, alternative medicine, religion, and forced compliance. The findings of the research endorse necessity of dialogue and participation within health communication strategies supporting the alternative dimension validates foregrounding and integrating culture at all stages of program development while addressing health crises. Cultural beliefs and values create strategic influences thereby shaping a sympathetic environment for [health] promotion and interventions programs. Keywords Health Communication: Poliomyelitis (Polio), The Culture Centered Approach; Constructivist Grounded theory; Poliovirus Vaccines; Vaccination Refusal; Immunization